Damage evolution and life modeling of hot corrosion environment on creep‐fatigue of a directionally solidified nickel‐based superalloy. Issue 4 (4th January 2023) - Hu, Jianhui; Zhao, Gaole; Li, Shaolin; Qi, Hongyu; Yang, Xiaoguang; Shi, Duoqi
Abstract: This study developed a corrosion‐creep fatigue‐life‐prediction methodology based on continuous‐damage mechanics (CDM). A systematic investigation of the turbine‐blade material DZ125 (a nickel‐based superalloy) was conducted, including oxidation and high‐temperature hot corrosion‐creep fatigue tests. Pre‐exposure experiments explained the damage process in DZ125. The applicability of the CDM‐based life‐prediction model of DZ125 was verified experimentally and by comparison with corresponding data from published studies. The model exhibited excellent life‐prediction ability for gas‐turbine hot‐section components vulnerable to cyclic loads and hot corrosion combined. Abstract : Highlights The time/rate dependence of viscoplastic behavior is expressed more accurately. Initial rapid cyclic softening and subsequent stable cyclic softening are described. The effect of nonproportional hardening on cyclic mechanical behavior is considered. The proposed model is verified by two materials with different damage types.